Multiple Legislative Candidates in Different Political Parties: Morality in the Perspective of Philosophy of Law - Budisetyowati, Dwi Andayani; Nainggolan, Indra Lorenly (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research analyzes the challenges associated with legislative candidates simultaneously registered by two distinct political parties and engaging in electoral processes. The requirement of a statement for a candidate to be nominated by only one political party in the general election needs to be revised to address the problem at hand. Efforts are needed to enhance the role of political parties participating in the election. Political parties face a challenging task as institutions authorized to register their members as legislative candidates. The institutional strengthening of the role of political parties in political recruitment is necessary. The selection process carried out by political parties aims to produce competent individuals prepared to assume public office. Apart from that, the moral attitudes of political party cadres as legislative candidates are tested before taking office. All mechanisms employed by political parties should be conducted democratically and with integrity. One proposed mechanism is to set a requirement that legislative candidates must have been members of a political party for at least five years. This five-year membership requirement should be introduced alongside the requirement for candidates to be nominated by only one political party. Consequently, it is imperative to amend the election law by including a provision that mandates a minimum five-year membership in a political party. This study adopts a normative juridical methodology underpinned by a conceptual framework guided by the relevant statutory regulations.